Transgenic plants regenerated from hairy roots of Nicotiana benthamiana: a promising host for transient expression of foreign proteins - Sindarovska, Y.R.; Gerasymenko, I.M.; Sheludko, Y.V.; Komarnytskyy, I.K.; Bannikova, M.A.; Kuchuk, N.V. (Цитология и генетика, 2005)
Hairy root cultures of Nicotiana benthamiana have been obtained by co-cultivation of leaf explants with Agrobacterium rhizogenes strain A4 harboring a binary vector plasmid, and transgenic nature of the obtained cultures was confirmed by PCR analysis. Transgenic plants were regenerated from hairy roots. The biomass yield of transgenic plants grown in vitro was almost two-fold higher than those of wild-type N. benthamiana plants. They differed from untransformed plants by short internodes, reinforced stem, thick and wrinkled leaves and more developed root system. The level of Agrobacterium-mediated transient expression of green fluorescent protein (GFP) in the regenerated plants was similar to that of untransformed plants. Культуры корней «hairy roots» Nicotiana benthamiana были получены кокультивированием листовых эксплантов со штаммом Agrobacterium rhizogenes А4, содержащим бинарную векторную систему, и трансгенная природа полученных линий корней была доказана методом ПЦР. Из трансгенных корней были регенерированы растения. Биомасса регенерированных растений, культивировавшихся in vitro, превышала биомассу нетрансформированных растений N. benthamiana приблизительно в два раза. Они отличались от интактных растений укороченными междоузлиями, утолщенным стеблем, толстыми искривленными листьями и более развитой корневой системой. Уровень Agrobacterium-опосредованной транзиентной экспрессии репортерного белка GFP в регенерованных растениях не отличался от такового у нетрансформированных растений.